Amyloid Assembly Endows Gad m 1 with Biomineralization Properties - Castellanos, Milagros; Torres-Pardo, Almudena; Rodríguez-Pérez, Rosa; Gasset, M. (Biomolecules, 2018)
Acid proteins capable of nucleating Ca2+ and displaying aggregation capacity play key roles in the formation of calcium carbonate biominerals. The helix-loop helix EF-hands are the most common Ca2+-binding motifs in proteins. Calcium is bound by the loop region. These motifs are found in many proteins that are regulated by calcium. Gad m 1, an Atlantic cod β-parvalbumin isoform, is a monomeric EF-hand protein that acts as a Ca2+ buffer in fish muscle; the neutral and acid apo-forms of this protein can form amyloids. Since Ca2+-nucleating proteins have a propensity to form extended β-strand structures, we wondered whether amyloid assemblies of an EF-hand protein were able to influence calcium carbonate crystallization in vitro. Here, we used the Gad m 1 chain as a model to generate monomeric and amyloid assemblies and to analyze their effect on calcite formation in vitro. We found that only amyloid assemblies alter calcite morphology. This work was supported by grants from the Spanish AEI/EU-FEDER SAF2014-52661-C3 and BFU2015-72271-EXP.